La insuficiencia de la Ley de Transparencia para el ejercicio del Periodismo de datos en España. - La-Rosa, Leonardo; Sandoval-Martín, Teresa (Revista Latina de Comunicación Social, 2016)
Introduction: Incorporating elements of the transparency's culture of the Big Data era in journalism has become into what is known as Data Journalism (DJ). Objectives: Since it depends on institutions outside journalism, we seek to determine to what extent the Spanish Transparency Law has affected the development of DJ and how this professional sector has responded to these affections. Methodology. We examined what elements of the Law affects DJ with in-depth interviews to data journalists. Through a Content Analysis in medias with data units, we determined how this sector has replied to these elements that affects them. Results and Conclusions. DJ in Spain hasn't reach its potential because of the insufficiency of the Law and its breach, which is why journalists have placed Transparency in the Public Agenda as a main theme.